COMPARATIVE EVALUATION OF INVITRO ANTIINFLAMMATORY ACTIVITY OF PSIDIUM GUAJAVA AND SYZYGIUM CUMINI LEAVES - Deepa, *Jose; Aleykutty, N A; Jyoti, Harindran (International Journal of Ayurveda and Pharma Research, 2017)
Psidium guajava L. known as Guava is a medicinal plant belonging to the family Myrtaceae. Syzygium cumini Linn. known as Jamun is a tropical tree belonging to the family Myrtaceae. Recent evidence has demonstrated that combination therapy could provide greater therapeutic benefits to diseases such as AIDS, cancer, atherosclerosis and diabetes, all of which possess complex etiology and pathophysiology that make the treatment difficult with single drug target approach. The present study was to compare the invitro anti-inflammatory activity of two plants from Myrtaceae family as well as to investigate the anti-inflammatory activity of the combined extracts (1:1mixture) of those plants by estimating the inhibition of cyclooxygenase, 5-lipoxygenase, cellular nitrite levels, inducible nitric oxide synthase and myeloperoxidase using RAW 264.7 cells. Total ethanolic extracts of shade dried leaves were prepared and subjected to invitro anti-inflammatory study. The percentage inhibition of COX and 5 LOX by the combined extract, at 100 µg/ml was 55.67 and 48.02 respectively. The reduction in the cellular nitrite level (393.195 µg) and MPO level (0.00205U/ml) was comparable to that of standard. The results of the study showed that at 100 µg/ml, the combined extract (1:1 mixture) of the plants exhibited prominent anti-inflammatory activity than either of the individual plants in all the methods studied. On comparison of the anti-inflammatory activity, Syzygium cumini is found to be more active than Psidium guajava. Hence the combination of the two plants can be used to formulate drugs for various inflammatory disorders in traditional and modern medicine.